Project-Based Learning: The Highlighting Teachers’ Views of Teaching English Language in Secondary Schools - Lutfiyana, Faza; Amalia, Lulu Laela; Pitaloka, Ashanti Dayani Ajeng; Novianti, Sri (Universitas Pendidikan Mandalika, 2024)
It has been two years since the Ministry of Education and Culture in Indonesia mandated an Emancipated curriculum to foster independent learning after the COVID-19 pandemic. All of the aspects and policies in school need to adapt to the new version of the learning and teaching process. The use of Project-based learning in this era is imperative things which can help students and teachers be more interactive in dealing with global skills. This approach can guide the teachers more easily understand the topic by using projects that relate to their workplace. This research is designed to investigate the teachers' views on practicing project-based learning in classroom activities. This case study used document analysis in the form of a lesson plan to check their understanding of project-based learning. The semi-structured interviews were also held to collect deep data analysis with two teachers at the secondary level who had already implemented project-based learning during the learning process. The findings showed that project-based learning can assist the teacher in developing an engaging and collaborative classroom that supports both the teachers' and students' capacity for critical Thinking. Interestingly, the study revealed that the teachers realized that the challenges in applying Project-based learning might derive from the number of meetings in one project.Â